Humans-with-internet or internet-with-humans: a role reversal? - Souto, Daise Lago Pereira; Borba, Marcelo de Carvalho (Revista Internacional de Pesquisa em Educação Matemática, 2018)
The aim of this article is to analyze possible influences of the internet on mathematics online distance education and to discuss the interrelationships between the human and non-human actors involved. To do so, we analyzed empirical data produced in a mathematics education course for teachers. The discussion is based on the approach of Activity Theory and on the construct humans-with-media. As an analysis tool, we used the notion of mini-cyclones of expansive transformation. The results indicated that the activity of “doing math online” developed two roles for the internet: artifact and community. This double role contributed to the transformation of the basis of the activity and leveraged distinct movements. In addition, we found that human and non-human actors interacted in such a way that both were able to play identical roles in an activity system.